This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
N → ∞ lim ( a = 0 ∏ N ( 1 + N a ) ) N + 1 1 = exp ln N → ∞ lim ( a = 0 ∏ N ( 1 + N a ) ) N + 1 1 where exp x = e x = exp N → ∞ lim ln ( a = 0 ∏ N ( 1 + N a ) ) N + 1 1 = exp N → ∞ lim N + 1 1 ln ( a = 0 ∏ N ( 1 + N a ) )
Using the rules of logarithms, = exp N → ∞ lim N + 1 1 a = 0 ∑ N ln ( 1 + N a )
Switch to integral notation with x = N a and d x = N 1 : = exp ( ∫ 0 1 ln ( 1 + x ) d x ) = e [ ( 1 + x ) ln ( 1 + x ) − 1 − x ] 0 1 = e 2 ln ( 2 ) − 1 = e 2 2 = e 4